Verbal redundancy aids memory for filmed entertainment dialogue - Hinkin, Michael P.; Harris, Richard J.; Miranda, Andrew T. (My University, 2014)
Three studies investigated the effects of presentation modality and redundancy of verbal content on recognition memory for entertainment film dialogue. U.S. Participants watched two brief movie clips and afterward answered multiple-choice questions about information from the dialogue. Experiment 1 compared recognition memory for spoken dialogue in the native language (English) with subtitles in English, French, or no subtitles. Experiment 2 compared memory for material in English subtitles with spoken dialogue in either English, French or no sound. Experiment 3 examined three control conditions with no spoken or captioned material in the native language. All participants watched the same video clips and answered the same questions. Performance was consistently good whenever English dialogue appeared in either the subtitles or sound, and best of all when it appeared in both, supporting the facilitation of verbal redundancy. Performance was also better when English was only in the subtitles than when it was only spoken. Unexpectedly, sound or subtitles in an unfamiliar language (French) modestly improved performance, as long as there was also a familiar channel. Results extend multimedia research on verbal redundancy for expository material to verbal information in entertainment media.
Keywords: Film entertainment; Memory; Subtitles; Verbal redundancy